USE OF GLYCEROL AT 8% CONCENTRATION DURING CYROPRESERVATION IS OPTIMAL FOR THE POST-THAW QUALITY OF CAUDA EPIDIDYMAL SPERMATOZOA OF RAM - AHMED, T; ISLAM, R (The Indian Journal of Animal Reproduction, 2016)
The cauda epididymal spermatozoa of ram recovered using incision method and showing progressive motility ≥70% were pooled and divided into aliquots before extension in Tris-Citric acid-Fructose-Egg yolk extender using glycerol at 4% (G4), 6% (G6) and 8% (G8) concentration as cryoprotectant. At post-thaw stage, the sperm motility was higher (P
Keywords: Cryopreservation; Glycerol; Post thaw; Ram; Spermatozoa